PEMAHAMAN DAN AKSEPTANSI PARA BANKIR BANK SYARIAH DAN MANAJEMEN LEMBAGA KEUANGAN SYARIAH TERHADAP PENDEKATAN ECONOMIC VALUE OF TIME UNTUK PRODUK MURABAHAH - Muhammad Akhyar Adnan, Nuroh Shobah Hanum (FE UMY, 2014)
This study aims at testing the understanding and acceptance of the Islamic bankers and Manager of Islamic Financial Institutions in Yogyakarta on the notions of the economic value of time for murabahah products.It is the alternative concept of time value of money which is widely understood and practiced by almost all Islamic Financial Institutions in the world. The research basically appliesthe mixed method, that is a simple descriptive quantitative andqualitative methods, which are also enriched with the criticaland interpretative approaches. The data were collectedof primarilyfrom direct interviews with 20 informen. They are bankers ofIslamic Banks and or Managers of Islamic Financial Institutions in Yogyakarta, which includes Islamic Banks (BUS), Rural Shariah Banks (BPRS) and Baitul Maal wat Tamwil (BMT). The results show that the understanding of Islamic Bankers and Managers of Islamic Financial Institutions in Yogyakarta of concept economic value of time is still relatively poor. However, the level of acceptance of the concept of economic value of times the bankers and Manager Islamic Financial Institutions is relatively high to be applied in the practices.